Food manipulation and processing in wild western gorillas of Central African Republic: implications for studying behavioural variability - Shelly Masi; Ellen JM Meulman; Françoise Aubaile; Sabrina Krief; Angelique Todd; Emanuelle Pouydebat (Revue de Primatologie)
Inter-group variability in food-processing techniques within species may involve subtle differences in grasping and manipulation of food items. Whereas traditional ethnographic approaches may help to identify some of this variation, more fine-scaled quantification of manipulative actions may be required to detect such behavioral variation in a more systematic and detailed manner. In this regard, relative to other great apes, gorillas are interesting because, like humans, they possess an elongated thumb that enables precision grips and finer manipulative actions, particularly important for bimanual coordination. Such manipulative abilities may induce fine-grain inter-individual variability in food-manipulation techniques and, when such techniques are socially transmitted, greater cultural diversity. Frame by frame video analysis (31 hours; 10 months during 2008–2009) of a habituated group (Number of individuals = 13) of western gorillas at Bai Hokou, Central African Republic, was used to investigate, food-manipulation strategies for different food types (e.g. leaves, stems, fruits), for the first time in this species. Results indicate that food features (e.g. size, shape, extraction requirements) affect individual food-manipulation strategies (e.g. number of fingers involved, hand preference, use of mouth), as well as the requirement of various functional strategies (e.g. grip types, postural sequences, repositioning behavior) during unimanual and bimanual processing. Systematic microanalysis of manipulative actions could thus provide us with a powerful tool to improve our assessment of foraging traditions and food-processing complexity across animal species and taxa.